Outcomes of surgical treatment of Peyronie's disease. (May 2014) - Carson, Culley C.; Levine, Laurence A.
Abstract : The aims of the present review were to assess the literature on published outcomes and complications associated with surgical treatments for Peyronie's disease (PD) and to assist clinicians in the effective management of PD by increasing understanding and awareness of the outcomes associated with current surgical treatment options. A PubMed literature search was conducted to identify relevant, peer‐reviewed clinical and review articles published between January 1980 and October 2013 related to outcomes of surgical correction of PD. Search terms for this non‐systematic review included 'Peyronie's disease', 'outcomes', 'complications', 'erectile dysfunction or ED', 'patient expectation', and 'patient satisfaction'; search terms were searched separately and in combination. Case studies and editorials were excluded, primary manuscripts and reviews were included, and bibliographies of articles of interest were reviewed and key references were obtained. Assessment of the study design, methodology, clinical relevance and impact on the surgical outcomes of PD was performed on the sixty‐one articles that were selected and analysed. Currently, there are several investigational minimally invasive and non‐surgical treatment options for PD; however, surgical treatment remains the standard of care for patients with stable disease and disabling deformity or drug‐resistant erectile dysfunction. Each of the different surgical procedures that are used for treatment of PD, including tunical shortening, tunical lengthening (plaque incisions or partial excision and grafting), and use of inflatable penile prostheses, carries its own advantages and disadvantages in terms of potential complications and postoperative satisfaction. Because of the variety of ways that PD may present in affected patients, no single, standard, surgical treatment for this disorder has prevailed and multiple variations of each type of procedure may exist. Surgical outcomes of the most commonly used procedures are not substantially different; therefore, the appropriateness of each treatment option may often depend on disease and patient characteristics (e.g. deformity and erectile function). Surgical algorithms have been published to guide surgeons and patients through the selection of surgical procedures in the absence of conclusive, long‐term outcome data. Accumulating data on outcomes associated with established procedures, modifications to these procedures, and new surgical techniques and materials may serve to further guide practice and refine evidence‐based selection of the surgical approach.